The Relationship Between Factors Affecting E-Wallets Adoption Among Adults in Kuantan, Pahang - Lim, Ru Jia; Zulkipli , Hafizah (Research in Management of Technology and Business, 2023)
An e-wallet is a digital wallet that allows users to make online purchases using mobile devices. E-Wallets are fully interactive cashless devices that may be used to replace physical cash notes. The primary goal of e-wallets is to make rapid transactions, which discourages individuals from using cash. However, some individuals still lack confidence in electronic payments. This study aimed to examine the relationship between factors affecting e-wallet adoption among adults in Kuantan. This study aims to explore the relationship between perceived ease of use, perceived usefulness, and security and the adoption of e-wallets among adults in Kuantan. The quantitative method was used in this research by using a questionnaire as a research instrument. The questionnaires were distributed to 300 respondents in Kuantan. According to the findings of the descriptive analysis, perceived usefulness was the main factor in e-wallet adoption among adults in Kuantan. Furthermore, perceived ease of use, perceived usefulness, and security have all been found to have a significant relationship with e-wallet adoption. The primary reason for adopting e-wallets was that customers found them highly convenient because they were available in many locations around Malaysia. This research provides a better understanding of the adoption of e-wallets. The limitations of this study included the inability to handle the situation, and the quantitative research outcomes were limited. This study provided some recommendations for future studies.